Analisis Gangguan Hasil Uji Pop Test Sebagai Parameter Kehandalan Mesin Diesel Lokomotif CC 206 - Henry Widya Prasetya; Dadang Sanjaya Atmaja; Rochmat Septian Hermawan (Virtual of Mechanical Engineering Article, 2021)
Locomotive CC 206 is the newest locomotive owned by PT Kereta Api Indonesia. Inside the CC 206 locomotive is equipped with a sophisticated smart display that can monitor all size parameters and damage to the locomotive itself. One of the capabilities of the CC 206 locomotive is the pop test. Pop test is the ability of the CC 206 locomotive to test the performance of each cylinder of the diesel engine. Based on the pop test results, there are various disturbances that often occur during maintenance of the CC 206 locomotive diesel engine.The purpose of this analysis is to analyze the pop test results as a reliability parameter on the CC 206 locomotive diesel engine, to analyze the factors causing the disturbance in the pop test results and analyze the effect of the failure of the pop test results on performance. Based on the results of the pop test, it was found that one of the cylinders was abnormal because the injector was under pressure, the injector spring was damaged and there was a clogged nozzle. Keyword: CC 206 Locomotive, Pop test, Maintenance.